Aspects of the epidemiology of Cassava brown streak disease in Tanzania - Rwegasira, Gration Mutashoberwa (My University, 2010)
In this study, the field diagnostic survey supplemented with CBSV detection by RT-PCR using virus coat protein gene-specific primers, revealed the presence of CBSD throughout the cassava growing areas of Tanzania. Sequence data of 43 CBSV isolates suggested considerable diversity among although the majority claded together. CBSV transmission was achieved through cutting tools with 22 % efficiency using test plants of susceptible cassava cv. Albert. Sap transmission of the virus had 54 % efficiency in cv. Mreteta. Grafting of CBSV-free susceptible scions onto CBSV-infected rootstocks was the most efficient transmission technique with up to 100 % recipient plants cv. Albert infected within 4- weeks after inoculation. The virus was not transmitted through infected root debris or seeds. Three major types of foliage and root symptoms for CBSD were apparent. The foliage symptoms included veinal chlorosis, chlorotic blotches and chlorotic spots. The internal root symptoms were brown necrotic mass, necrotic specks and chalky necrosis in the root cortex. The nature of occurrence of these symptoms was also elucidated. The tender leaves, youngest symptomatic leaves and non-necrotic portions of the root cortex were suitable for detection of the virus by RT-PCR. CBSV-free plants could not be regenerated from CBSV-infected cuttings. Foliage chloroses were found to be suggestive but not an absolute indication of CBSV infection. Only 67 % of tested field samples were both symptomatic and infected by the virus; 22 % were CBSV-free despite being symptomatic; 7 % were infected but symptomless; 4 % were CBSV-free and symptomless. CBSD incidences and severities in different cultivars varied between seasons and were dependent on the inherent cultivar characteristics. Foliage and stem CBSD incidences and severities were significantly (P < 0.001) related to the individual cultivars. The effect of plant age iv on CBSD incidences and severities was also significant (P < 0.05). Low temperature (260C day and 180C night temperature) was critical and lethal to CBSD-affected plants. More than 50 % and 100 % of test plants died within 30 and 50 days respectively, post-exposure to this temperature. Moisture stress led to deaths of all CBSD-affected test plants within 90 days.